PENERAPAN SANKSI ADAT NGOMPANGK DALAM MASYARAKAT DAYAK JANGKANG TANJUNG DI DESA SUNGAI MAWANG KABUPATEN SANGGAU - NIM. A1011191081, PETRONIUS SEPTO JUMIARDI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The custom of pregnancy outside of marriage or the Ngompangk custom is one of the customary sanctions that exist in the customary law of the Dayak Jangkang Tanjung in Sungai Mawang Village, Mukok District, Sangggau Regency. Nowadays, violations of the Ngompangk custom are widespread, especially among young people. Ngompangk or pregnancy outside of marriage, in this case, is considered taboo because it is a bad act that tarnishes the good name of the family and hurts the hearts of the indigenous community because it does not respect their ancestors. The problem in this research is that the application of sanctions to perpetrators who violate the ngompangk custom has not been fully implemented according to customary provisions, this is because there are several factors that trigger the act of ngompangk in that place. he formulation of the problem in this research is